Computational tools and resources for prediction and analysis of gene regulatory regions in the chick genome. Issue 5 (30th March 2013) - Khan, Mohsin A.F.; Soto‐Jimenez, Luz Mayela; Howe, Timothy; Streit, Andrea; Sosinsky, Alona; Stern, Claudio D.; Burt, David W.; Farlie, Peter G.
<x xml:space="preserve">Abstract</x> The discovery of cis‐regulatory elements is a challenging problem in bioinformatics, owing to distal locations and context‐specific roles of these elements in controlling gene regulation. Here we review the current bioinformatics methodologies and resources available for systematic discovery of cis‐acting regulatory elements and conserved transcription factor binding sites in the chick genome. In addition, we propose and make available, a novel workflow using computational tools that integrate CTCF analysis to predict putative insulator elements, enhancer prediction, and TFBS analysis. To demonstrate the usefulness of this computational workflow, we then use it to analyze the locus of the gene Sox2 whose developmental expression is known to be controlled by a complex array of cis‐acting regulatory elements. The workflow accurately predicts most of the experimentally verified elements along with some that have not yet been discovered. A web version of the CTCF tool, together with instructions for using the workflow can be accessed from http://toolshed.g2.bx.psu.edu/view/mkhan1980/ctcf_analysis. For local installation of the tool, relevant Perl scripts and instructions are provided in the directory named "code" in the supplementary materials. genesis 51:311–324. © 2013 Wiley Periodicals, Inc.